The Effect of Plyometric Training with Extra Weights On the Development of Some Physiological Varisbilities of Football Player- Juniors (Raparin Journal of Humanities (RJH), 2025)
The research aims to prepare a training curriculum with plyometric exercises and extra weights for the junior category, and to identify the impact of this training program in developing of some physiological varisbilities, as well as to identify differences between the results of the pre and post test in the first and second experimental groups in the development of some physiological varisbilities, and to identify differences in the results Post-test between the first and second  experimental groups in developing  of some physiological varisbilities.The research problem appears in the lack of use of exercises that improve the muscular strength of football players, which may cause a clear discrepancy in the level of the general performance of the team, and most of the exercises were traditional or random, and the researcher believes that adding weights with plyometric exercises may improve strength significantly. Plyometric training by adding weights through the design of a training curriculum using plyometric exercises to find out the impact on the development of some physiological varisbilities.The researcher uses the experimental method by using two groups (the first and the second) in the pre and post tests due to its suitability and the nature of the problem. The researcher deliberately selected the research community from the players of the junior team in the Chwarqurna Sports Club Academy, which is represented by (45) players, and (25) players were chosen randomly by drawing lots to conduct the main experiment on them, and (5) players were excluded for not committing to training during a period The experiment, and the research sample was divided by the intentional method into two groups (the experimental one and the second one) with (10) players in the first experimental group and (10) players in the second experimental group. The researcher reached the latest proposed training curriculum for development in all physiological varisbilities under investigation except (anoxic capacity, pulse rate before exertion) in the first group, and (anoxic capacity, pulse rate before and after exertion, respiratory rate after exertion) in the second group.